REFLECTIONS ON CIVIL LIABILITY FOR DAMAGES CAUSED BY UNMANNED AIRCRAFTS - Pusztahelyi, Réka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
As the competence of the EU has been extended to cover the regulation of all drones involved in international air navigation regardless of their maximum take-off masses, and in accordance with the Single European Sky concept, a new Regulation (EU) 2018/1139 of the European Parliament and Council (Regulation) came into force in August 2018 regarding common rules in the field of civil aviation that also addresses the main questions relating to the utilisation of unmanned aircrafts, i.e. drones. While the Regulation and the implementative acts were elaborated, and comprehensive regulation at the EU level is becoming complete, the civil liability issues related to drone usage seem to remain on the national level, with the exeption of the Product Liability Directive, provided that the cause of the drone accident was the defect of the product. In this essay, the Hungarian strict liability statute, the rule of liability for highly dangerous activity, will be examined, especially from the viewpoint of the dangerousness of the activity, in order to assess how it can be applied to drone utilisation in the future.